The Significance of Stone Analysis, Metabolic Evaluation and Their Effect on Metaphylaxis: The Results from Tekirdağ Province - Mehmet Fatih ŞAHİN; Cenk Murat YAZICI; Rıdvan ÖZCAN; Çağrı DOĞAN; Murat AKGÜL (Namık Kemal Tıp Dergisi, 2025)
Aim: The aim of this study is to present the results of stone analysis and metabolic evaluation in Tekirdağ province, determine the demographic and personal characteristics and relationships of patients with these, and reveal their effects on metaphylaxis. Materials and Methods: The data of 312 patients with urinary system stone disease (USD), who applied to our clinic between August 2018 and January 2021, were analyzed. Stone analysis was performed on these patients using the spectroscopic method. The metabolic evaluation was performed in 24-hour urine and plasma simultaneously on 156 patients with high risk. Age, gender, body mass index, stone localization, stone density (HU), volumes, and 24-hour urine and serum plasma of the patients were evaluated. Results: The USD was found predominantly in males, in multiple locations in the urinary system, frequently as a single stone, with sterile urine culture. The most frequently detected stone type was calcium oxalate; the least common type of stone was xanthine. The highest mean HU was in calcium oxalate stones, and the lowest was in uric acid + ammonium urate stones. As the calcium content increased, the HU of the stone increased. Hypercalciuria was the most common abnormality in urine, while hyperuricemia was the most common and hypercalcemia the least common abnormality in plasma. Potassium citrate was used most frequently for metaphylaxis. The rate of potassium citrate metaphylaxis in appropriate patients was 43.3%, and the recurrence rate in these patients was 20%. Conclusion: Metabolic evaluation and stone analysis provide valuable data about USD patients. Urologists should evaluate and apply them more frequently, as these data may minimize stone-related interventions via metaphylaxis.